A Review of Biofuels and Their Positive Impacts on Health and the Environment - Yuliana, Maria; Ismadji, Suryadi; Wijaya, Christian Julius; Soetaredjo, Felycia Edi; Lie, Jenni; Hartono, Sandy Budi; Irawaty, Wenny; Puspitasari, Nathania; Lourentius, Suratno (Widya Teknik, 2024)
Indonesia's high population and rapid economic growth are driving a major transformation in the transportation sector, which is in line with the high increase in fuel demand. The need for biofuel as a substitute for conventional fuel is increasingly being prioritized by considering sustainable development goals (SGDs). Biofuel has safer health and environmental impacts than conventional fuel but still has fuel performance that meets fuel standards and engine performance. Biofuels can be derived from a variety of more sustainable and abundant raw materials, such as biomass and vegetable oils. In this review biodiesel, hydrogenated vegetable oil (HVO), and direct vegetable oil (SVO) are discussed in depth regarding the transformation of their production processes and their impacts on health and the environment. Biodiesel is one of the most widely developed and implemented compared to HVO and SVO to encourage the use of renewable energy in various aspects of people's lives in Indonesia. These three biofuels have different fuel characteristics and performance but can continue to be developed in the future to increase the implementation of renewable energy more massively.